The Effectiveness of Agrarian Reform Policy in Improving the Welfare of Farmers in Beji Village, Gunungkidul - Davina Nurfadilah (Indonesian Journal of Agrarian Law, 2026)
Farmers' poverty is a structural problem that still dominates rural areas, including Beji Village, Gunungkidul Regency. This study aims to analyze the factors that cause farmers' poverty and evaluate the implementation of agrarian reform policies in efforts to alleviate poverty in the agricultural sector. The research method used is legal sociology with a normative and empirical approach through interviews and field observations. The results of the study show that farmer poverty is influenced by the agroecological conditions of karst areas that are prone to drought, limited land ownership, low access to capital and technology, limited human resource quality, and weak management of agricultural production facilities. The implementation of agrarian reform policies in Beji Village has provided benefits in the form of land access for farmers, but has not been optimal in reducing poverty due to legal uncertainty over land and limited post-agrarian reform access regulations. Therefore, agrarian reform needs to be integrated with farmer empowerment policies in order to improve sustainable welfare.